2016
DOI: 10.1007/s12178-016-9340-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional knee assessment with advanced imaging

Abstract: The purpose of anterior cruciate ligament (ACL) reconstruction is to restore the native stability of the knee joint and to prevent further injury to meniscus and cartilage, yet studies have suggested that joint laxity remains prevalent in varying degrees after ACL reconstruction. Imaging can provide measurements of translational and rotational motions of the tibiofemoral joint that may be too small to detect in routine physical examinations. Various imaging modalities, including fluoroscopy, computed tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Additionally, individuals with cruciate ligament degeneration present with greater severity of cartilage damage, bone marrow lesions, subchondral cysts, and lateral meniscus pathology when compared to individuals with normal cruciate ligaments [33]. While we are unable to make definitive claims based on our results, cruciate ligament degeneration could be early evidence of a maladaptation to loading or due to aberrant joint loading created by impaired ligamentous function that increases knee instability or laxity [34]. Future studies are needed to confirm whether the presence of knee instability increases the risk for incident AKOA.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, individuals with cruciate ligament degeneration present with greater severity of cartilage damage, bone marrow lesions, subchondral cysts, and lateral meniscus pathology when compared to individuals with normal cruciate ligaments [33]. While we are unable to make definitive claims based on our results, cruciate ligament degeneration could be early evidence of a maladaptation to loading or due to aberrant joint loading created by impaired ligamentous function that increases knee instability or laxity [34]. Future studies are needed to confirm whether the presence of knee instability increases the risk for incident AKOA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this study used static loaded MRI, which is not a complete true representation of walking or other more complex motions . However, it is very difficult to take accurate motion MRI measurements due to decreased resolution . Instead, we scanned the knees at extension to capture them at midstance with loading in attempt to simulate the natural weight bearing aspect of walking.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanically, the ankle, with its high congruency, acts as a rolling joint with high congruency (22). The knee, however, acts as a rolling, sliding, and rotating joint during motion (24). This is the principal difference for increased cartilage degeneration and the high rate of primary OA in the knee.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, among individuals aged between 21 and 39 years, there are 10 who scored AOFAS = <19. More than double(24) are present in the age class[40, 59]. Furthermore we found that the number of normal weight patients is always superior to obese class I patients except in patients 40-59 y.o.…”
mentioning
confidence: 85%